MATHEMATICS PROBLEM-SOLVING ABILITY FOR FOURTH GRADE STUDENTS OF SDN 2 TONATAN BY USING THE PMRI APPROACH - Kurnia Hidayati; Ahmad Zubaidi (Ibriez: Jurnal Kependidikan Dasar Islam Berbasis Sains)
Problem solving is one of the basic mathematical abilities that students must master. To develop these abilities, education must direct students towards the use of various situations and opportunities in rediscovering mathematics in their own way. One approach that can be used is the Indonesian Realistic Mathematics Education (PMRI). PMRI also emphasizes bringing mathematics to meaningful teaching by linking it to everyday life that is realistic. The conclusion of this research is 1) The ability to solve math problems of grade IV SDN 2 Tonatan students (the experimental class after using the PMRI approach) is moderate. 2) The ability to solve math problems of fourth grade students of SDN 2 Tonatan (control class that does not use the PMRI approach) is moderate. 3) There is a difference in the mathematical problem solving ability of grade 4 students of SDN 2 Tonatan between before and after using the PMRI approach with tcount > ttable or 8,903 > 2,8 at a significance level of 5 % and 2)There is a difference in the mathematical problem solving ability of grade 4 students of SDN 2 Tonatan between those who use and do not use the PMRI approach with tcount > ttable or 2,79 > 2,02 at a significance level of 5 %.